Quantum computer simulator based on qutrits and the circuit model of quantum computation - Kaonain, Md. Shamsul (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.